Atomistic simulation of bicrystal behaviour with Σ5 grain boundary parallel to nanometric cutting direction. (23rd June 2022) - Hosseini, Seyed Vahid; Heidari, Mehdi; Parvaz, Hadi; Vahdati, Mehrdad
Molecular dynamics simulations were performed to study the behaviour of bicrystals in the nanometric cutting process with symmetric Σ5(210) grain boundary. Several copper bicrystals with various grains sizes were simulated using embedded atoms potential. Results showed that when a grain boundary was located at a high hydrostatic pressure area, at upstream of the cutting tool, it was diffused to lower grain by hydrostatic pressure. On the other hand, the grain boundary located at downstream of the tool was migrated to the machined surface with the evaluation of crystallographic orientation in adjacent atoms structure. Although in bicrystals with parallel grain boundary, defects initiate from tool edge similar to single crystals, defects propagation was significantly increased in bicrystal substrate caused the increment of plastic deformation and potential energy. Finally, these defects merged to grain boundary without transmission or reflection into the adjacent grain, increasing stress concentration and residual stress.